A rare case report: desmoid-type fibromatosis - Nadire Küçüköztaş; Elif Başaran; Yunus Emre Eksert; Melike Dereli (Northwestern Medical Journal)
Desmoid tumors, also known as desmoid-type fibromatosis (DF), develop from musculoaponeurotic tissues. They are Mesenchymal tumorfibrous tumors of benign character that do not metastasize. However, they can take an aggressive course by showing local growth in the area where they are located. Although they can originate fromany skeletal muscle, they are most commonly seen on the anterior abdominal wall. Various treatment options are available depending on the clinical condition of the patient. We aimed to discuss the diagnosis and treatment of DF with a 55-year-old male patient who has DF and applied to our clinic.